Manajemen Team Teaching Mata Kuliah Kepramukaan di Program Studi Pendidikan Dasar Islam - Rustam Supriyanto; Farhan Farhan (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2020)
This article explains the importance of collaboration and synergy in teaching team management between lecturers and scout trainers to realize the achievement of scouting mastery learning ins Study Program of Islamic Elementary Education(PGMI). This research is a literature review with a conceptual approach. The selection and sorting of relevant data is carried out and then analyzed in a descriptive qualitative manner. The research formulation is how the team teaching management of scouting courses in Islamic elementary education courses? The result of the study states : first; teaching team is started and based on the MoU between study programs or faculties stake holders and scout coaches. Second; teaching teams of scouting collaborate continuously in the implementation or education of basic and advanced courses. Third; teaching team of strengthening the role of the education and training center as well as research and development in research and public service in scouting. Fourth; teaching team in distribution evaluation of Scoutmaster students to group of siaga and penggalang as a test of the competency of professional teacher candidates on an ongoing basis.